A Study on Understanding Reinvestment Allowance Among Inland Revenue Board of Malaysia Officers in Klang Valley - Mohd Shukri, Saad (2024)
This study was conducted to find out the level of understanding of Reinvestment Allowance (RA) among officers of the Inland Revenue Board of Malaysia (IRBM) in the Klang Valley. RA is a fiscal incentive aimed at promoting business expansion, modernization, automation, and diversification, which are crucial for economic growth. The study used a qualitative method by conducting interviews with 20 IRBM officers through an online platform. Through thematic analysis, this research reveals various points of view, explaining the factors that influence the interpretation and implementation of RA. Preliminary findings show a variable level of understanding of RA among officers, with a notable disparity between those with years of experience in taxation and newer officers. Factors influencing understanding include the frequency of professional training, the complexity of regulations, and the availability of resources and guidance materials. The study concludes that while there is foundational awareness of RA among IRBM officers in Klang Valley, there is a need for enhanced and ongoing education to ensure comprehensive understanding and effective implementation of RA policies. Recommendations include developing targeted training programs, improving access to informational resources, and implementing regular workshops and seminars. These measures are expected to improve the administration and uptake of reinvestment allowances by businesses in Malaysia.